2014
DOI: 10.3892/ol.2014.2827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three common IL-17 single nucleotide polymorphisms on the risk of developing gastric cancer

Abstract: Abstract. A 1:1 matched case-control study was conducted to analyze the association between three common interleukin (IL)-17A and IL-17F single nucleotide polymorphisms (SNPs) and the risk of developing gastric cancer. Genotyping of SNPs rs2275913, rs763780 and rs3748067 within the IL-17 gene were detected by performing polymerase chain reaction-restriction fragment length polymorphism analysis. Gastric cancer patients were more likely to be cigarette smokers, alcohol drinkers and have a family history of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 21 publications
0
18
1
Order By: Relevance
“…For the correlation between IL-17 gene polymorphisms and development of gastric cancer, several previous studies have reported their association (Rafiei et al, 2013;Qinghai et al, 2014;Wang et al, 2014;Zhang et al, 2014;Gao et al, 2015;Hou and Yang, 2015;Qi et al, 2015), but they also reported inconclusive results. Zhang et al (2014) conducted a study in a Chinese population and found that the rs2275913 G > A and rs763780 T > C polymorphisms contributed to the development of gastric cancer.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…For the correlation between IL-17 gene polymorphisms and development of gastric cancer, several previous studies have reported their association (Rafiei et al, 2013;Qinghai et al, 2014;Wang et al, 2014;Zhang et al, 2014;Gao et al, 2015;Hou and Yang, 2015;Qi et al, 2015), but they also reported inconclusive results. Zhang et al (2014) conducted a study in a Chinese population and found that the rs2275913 G > A and rs763780 T > C polymorphisms contributed to the development of gastric cancer.…”
Section: Discussionmentioning
confidence: 84%
“…Wang et al (2014) conducted a case-control study in a Chinese population and suggested that rs2275913 and rs3748067 polymorphisms were correlated with an increased risk in a Chinese population. Gao et al (2015) conducted a study in a Chinese population and reported rs763780 T > C was correlated with risk of gastric cancer, but also reported that no association was identified between rs2275913 and rs3748067 polymorphisms and the risk of gastric cancer. Our study reported some similar results with the previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-17A rs2275913 and IL-17F rs763780 are two common SNP loci in the IL-17 genes, and these two SNPs could influence the transcriptional regulation of IL-17. Previous studies have reported an association between IL-17A rs2275913 and IL-17F rs763780 and various diseases, such as inflammatory bowel disease, osteoarthritis, tuberculosis, and cancers (Zhang et al, 2013;Han et al, 2014;Bulat-Kardum et al, 2015;Gao et al, 2015). However, only two previous studies have reported an association between the IL-17A gene polymorphism and cardiovascular disease (Pei et al, 2009;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 79%
“…The rs2275913 single nucleotide polymorphism (SNP) was identified in IL-17A and has been reported to be associated with various types of cancer, such as hepatocellular carcinoma, acute myeloid leukemia, colorectal cancer, cervical cancer, and bladder cancer (Quan et al, 2012;Zhou et al, 2013;Omrane et al, 2014;Wróbel et al, 2014;Xi et al, 2015). Many studies have linked the IL-17 rs2275913 SNP to gastric cancer, but their results are inconsistent (Wang et al, 2014;Gao et al, 2015;Hou and Yang, 2015;Long et al, 2015). In our study, we performed a hospital-based case-control study to assess whether the IL-17 rs2275913 genetic variation could influence susceptibility to gastric cancer in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%